Dietary α-tocopheryl acetate on fillet quality of tilapia - Fogaça, Fabiola Helena Dos Santos [UNESP]; Sant'Ana, Léa Silvia [UNESP]; Carneiro, Dalton José [UNESP] (Universidade Estadual de Maringa, 2009)
This work compared the effects of dietary α-tocopheryl acetate on storage life of tilapia fillets. Three experimental diets containing increasing a-tocopherol levels (zero, 100, and 200 mg kg-1) were used. The fish, with a mean initial weight of 184.23 ± 1.68 g, were fed diets for 63 days. After that period, they were slaughtered, filleted, and the fillets were grounded to accelerate lipid oxidation. Fish growth, survival, fillet yield, chemical composition and lipid oxidation of tilapia ground fillets were evaluated 0, 30 and 60 days after frozen storage. The results demonstrated that there was no significant difference between treatments for performance, and also, tocopherol did not influence the chemical composition values of fillets. Increased tocopherol levels in the feeds promoted a reduction in ground fillets lipid oxidation values.
Keywords: Lipid oxidation; Oreochromis niloticus; Storage life; Tocopherol\ supplementation; Tilapia